Role of the growth step on the structural, optical and surface features of TiO2/SnO2 composites. Issue 1 (9th January 2019) - Rimoldi, Luca; Meroni, Daniela; Pargoletti, Eleonora; Biraghi, Iolanda; Cappelletti, Giuseppe; Ardizzone, Silvia
Abstract : TiO2 /SnO2 composites have attracted considerable attention for their application in photocatalysis, fuel cells and sensors. Structural, morphological, optical and surface features play a pivotal role in photoelectrochemical applications and are critically related to the synthetic route. Most of the reported synthetic procedures require high-temperature treatments in order to tailor the sample crystallinity, usually at the expense of surface hydroxylation and morphology. In this work, we investigate the role of a treatment in an autoclave at a low temperature (100°C) on the sample properties and photocatalytic performance. With respect to samples calcined at 400°C, the milder crystallization treatment promotes anatase phase, mesoporosity and water chemi/physisorption, while reducing the incorporation of heteroatoms within the TiO2 lattice. The role of Sn content was also investigated, showing a marked influence, especially on the structural properties. Notably, at a high content, Sn favours the formation of rutile TiO2 at very low reaction temperatures (100°C), thanks to the structural compatibility with cassiterite SnO2 . Selected samples were tested towards the photocatalytic degradation of tetracycline in water under UV light. Overall, the low-temperature treatment enables to tune the TiO2 phase composition while maintaining its surface hydrophilicity and gives rise to well-dispersed SnO2 at the TiO2 surface.